Ecological Footprint and Carbon Footprint Analysis to Assess the Sustainability of the Barong Tongkok Region Spatially - Andrew Gilberd Fredrik Mulu; Joni Hermana; Arie Dipareza; Abdu Fadli Assomadi (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Barong Tongkok Subdistrict, West Kutai Regency, East Kalimantan, is experiencing increasing ecological pressure driven by population concentration, land-use change, and rising resource consumption, raising concerns about the region's environmental carrying capacity and long-term sustainability. Objective: This study aims to assess regional sustainability in Barong Tongkok Subdistrict using a spatially explicit approach that integrates the Ecological Footprint (EF), Carbon Footprint (CF), and Biocapacity (BC). Method: A quantitative approach was applied using household consumption surveys, land-cover data, emission factors, and Geographic Information Systems (GIS). The EF was calculated based on food consumption, resource use, and built-up land. The CF was estimated from household electricity consumption, LPG use, transportation fuel, and waste burning. BC was derived from land-cover-based productivity using yield and equivalence factors. Sustainability was evaluated through a Sustainability Index (SI), defined as the ratio between BC and the combined EF and CF. Result: The results indicate significant spatial variation in sustainability across villages. Geleo Baru Village exhibits the highest SI value (31.57), reflecting a strong ecological surplus supported by extensive natural land cover and low population pressure. Conversely, Rejo Basuki Village records the lowest SI value (0.023), indicating a severe ecological deficit due to limited land availability and intensive residential land use. Peripheral villages tend to show ecological surplus, while densely populated areas exceed local carrying capacity. Conclusion: The integration of EF, CF, and BC within a GIS framework effectively reveals spatial sustainability patterns, providing valuable insights for evidence-based regional planning and targeted strategies to improve local sustainability.